2011
DOI: 10.1016/s1473-3099(11)70098-6
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and efficacy of the HVTN 503/Phambili Study of a clade-B-based HIV-1 vaccine in South Africa: a double-blind, randomised, placebo-controlled test-of-concept phase 2b study

Abstract: Summary We report the primary analysis of the safety and efficacy of the MRKad5 gag/pol/nef HIV-1 sub-type B vaccine in South Africa (SA), where the major circulating clade is sub-type C. Methods This phase IIb double-blind, randomized test-of-concept study was conducted in sexually active HIV-1 sero-negative participants in SA. The co-primary endpoints were a vaccine-induced reduction in HIV-1 acquisition or viral-load setpoint. These were assessed independently in the modified intent-to-treat (MITT) cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
307
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(322 citation statements)
references
References 31 publications
6
307
0
4
Order By: Relevance
“…78). The increased risk correlated with prevaccination antibody titers to Ad5 in uncircumcised men who have sex with men (13)(14)(15)48). Subsequently, the HVTN-505 trial was designed to control for these factors, and the vaccine also included Env to enable the production of potentially protective antibodies (16).…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 99%
See 3 more Smart Citations
“…78). The increased risk correlated with prevaccination antibody titers to Ad5 in uncircumcised men who have sex with men (13)(14)(15)48). Subsequently, the HVTN-505 trial was designed to control for these factors, and the vaccine also included Env to enable the production of potentially protective antibodies (16).…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 99%
“…These central features distinguish the path to an HIV vaccine from the traditional design principles that led to successful vaccines against other infectious agents. The inability of these principles to yield an HIV vaccine became abundantly clear in six large HIV vaccine trials, where efficacy was not observed (11)(12)(13)(14)(15)(16) (Table 1). Strikingly, vaccination increased the risk of infection in two of these studies that selectively targeted T-cell immunity (13)(14)(15), providing a stark contrast between the development of conventional and HIV vaccines.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Education, identification and treatment of infected persons with antiretroviral drugs, male circumcision, condoms, and needle exchange programs have been effective at curtailing the epidemic, but declines in the rate of new infections have plateaued, and it appears unlikely that the goal of <500 000 new adult infections per year will be achieved by 2020. An effective HIV‐1 vaccine could contribute to further reductions of infections as part of a coordinated prevention strategy,2 but to date, testing of candidate vaccines in efficacy trials has been disappointing 3, 4, 5, 6, 7 with only one trial showing any degree of vaccine efficacy 8…”
Section: Introductionmentioning
confidence: 99%